Análisis de confiabilidad usando el método de Monte Carlo en los alimentadores principales de la subestación Cristianía perteneciente a la Empresa Eléctrica Quito. - Rivera Plaza, Dayana Joselyne (2020)
The faults in the Electrical Distribution System (SED) of the Quito Electric Company's primary feeder, which is produced by various cause, power outages for users that reduce the efficiency of the SED in relation to reliability; this research is therefore carrying out a reliability study in the primary distribution system of the scope of Cristianía with the Monte Carlo method for optimizing the continuity of electrical service for which the information of the main suppliers mentioned above for the period 2014-2020 and so with the data obtained the simulation of the Monte Carlo method is developed, taking into account the operating states, based on the generation of uniformly distributed random numbers for the calculation of forced availability (A) and unavailability (U) in order to obtain reliability indices at the load point for the period 2021-2023. The results of the reliability study show minimal variations with respect to the applicable methodologies, the Monte Carlo simulation method shows a greater accuracy, considering that for forced unavailability the variation is 0.00002 on average, so with the information obtained it is useful as a starting point to project which of the primary feeders has the highest probability of failure and to establish recommendations to the Quito Electricity Company to improve the reliability of the electricity supply.